A Qualitative Examination of Collaborative Infrastructure within Sexual Assault Response Teams. Issue 1 (6th April 2021) - Wegrzyn, Annie; Greeson, Megan R.; Mihelicova, Martina
Abstract: Sexual assault response teams (SARTs) are multidisciplinary interventions that seek to improve the response to sexual assault in their community. SARTs bring together relevant stakeholders (e.g., sexual assault advocates, medical/forensic examiners, police, prosecutors) to coordinate the response to sexual assault and improve survivors' help‐seeking experiences. SARTs may adopt various infrastructures to guide their team (e.g., case review, subcommittees), but little is known about how infrastructure influences SART effectiveness. Therefore, this qualitative study examined the helpful versus challenging aspects of SART infrastructure. Interviews from a national random sample of 169 SART leaders revealed helpful versus challenging aspects of mission statements, formal protocols, subcommittees, team roles, trainings, meetings, and case review. Participants believed infrastructures have positive influences on interdisciplinary relationships, team efficiency, and creating improvements in responding to sexual assault. However, certain infrastructures were difficult to implement for some teams. Additionally, some infrastructures can have unintended consequences, such as exacerbating team conflict. Findings suggest that SARTs may benefit from first focusing on infrastructures that build trusting interdisciplinary relationships and widespread buy‐in prior to implementing accountability‐focused measures (e.g., protocols, case review). Highlights: We examined how sexual assault response team leaders believe infrastructure relates to multidisciplinary team effectiveness. Example infrastructures included trainings, meetings, protocols, and case review. Infrastructure aided communication, role knowledge, shared power, efficiency, and response to cases. Accountability‐focused infrastructures can be challenging to implement and can exacerbate conflict.